Flash sales, bundling offers, and purchase intention: Examining the mediating effect of word of mouth in retail consumers - Anggraini, Maretha; Harinie, Luluk Tri; Sukmani, Meylinda; Meitiana, Meitiana (Journal of Management and Digital Business, 2026)
This study aims to analyze the effect of flash sales and bundling offers on consumers’ purchase intention, with Word of Mouth (WOM) serving as a mediating variable at Toko Columbus Sampit Branch. The research employed a quantitative approach using a causal associative method. The population consisted of 1,200 active consumers, and a sample of 300 respondents was selected using the Slovin formula and a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares (PLS). The results indicate that flash sales and bundling offers have a significant effect on consumers’ purchase intention. Furthermore, Word of Mouth (WOM) was found to mediate the relationship between flash sales, bundling offers, and purchase intention. These findings suggest that promotion strategies based on urgency and added value, reinforced by consumer-to-consumer communication, can enhance the effectiveness of offline retail marketing strategies.